Problems of Judicial Review in the Model of Democracy under the Thai Constitution B.E. 2560 - Yangsri, Chayapad (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2021)
This academic article aim to study the problem of the judicial review in a democratic model. Both in term of process and content. The results showed that the problem of judicial review power in a procedural democratic model is use of the majority in the exercise of decision power in opposition to the majority of the people in expressing their intention to draft a law in accordance with the Constitution, 2017, Article 77, which advocates for the deficiencies of the majority, both procedural imperfections. Lack of participation and equality in terms of content the legislature’s intentions do not match the views of the Thai people and the rights of the people, neglect the rights of minorities to lead. It is defined as the role of the judiciary in considering amendments. Therefore, it is seen that proceedings are mainly based on the opinion of the judges. Without considering the views of other groups.